Increasing student retention among college students - Neumann, Hillar (University of Wisconsin--Stout. Research Services, 2014)
Retention among college students is one of the biggest challenges facing colleges today. This research combines mixed qualitative and quantitative methods to determine factors that might allow colleges to better retain students. I find early risk indicators of students dropping out of college, and also some factors which serve as signals that can lead to retaining a student. Using statistics from a medium-sized Midwestern state institution, and combining them with student interviews, I find that academic support mechanisms, student GPA, and scholarships are the major factors affecting student retention.
Research article with table.
Keywords: student retention; Dropouts--Prevention; College students